Effects of Vitamin D and K on Interleukin-6 in COVID-19 - Visser, Margot P. J.; Dofferhoff, Anton S. M.; van den Ouweland, Jody M. W.; van Daal, Henny; Kramers, Cornelis; Schurgers, Leon J.; Janssen, Rob; Walk, Jona (Frontiers in Nutrition, 2022)
Background Pathology during COVID-19 infection arises partly from an excessive inflammatory response with a key role for interleukin (IL)-6. Both vitamin D and K have been proposed as potential modulators of this process. Methods We assessed vitamin D and K status by measuring circulating 25-hydroxyvitamin D (25(OH)D) and desphospho-uncarboxylated Matrix Gla-Protein (dp-ucMGP), respectively in 135 hospitalized COVID-19 patients in relation to inflammatory response, elastic fiber degradation and clinical outcomes. Results Comparing good and poor disease outcomes of COVID-19 patients, vitamin 25(OH)D levels were not significantly different. IL-6 levels, however, were significantly higher in patients with poor outcome, compared to patients with good outcome (30.3 vs. 153.0 pg/mL; p<0.0001). Dp-ucMGP levels as biomarker of extrahepatic vitamin K status was associated with IL-6 levels (r=0.35; p<0.0001). In contrast, 25(OH)D levels were only borderline statistically significant correlated with IL-6 (r=-0.14; p<0.050). A significant association was also found between IL-6 and elastic fiber degradation. Contrary to vitamin K status, 25(OH)D did not correlate with elastic fiber degradation. Conclusions Dp-ucMGP associates with IL-6 as a central component of the destructive inflammatory processes in COVID-19. An intervention trial may provide insight whether vitamin K administration, either or not in combination with vitamin D, improves clinical outcome of COVID-19.